2013
DOI: 10.5014/ajot.2013.004929
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Interventions to Improve the Reading Ability of Older Adults With Low Vision: A Systematic Review

Abstract: This systematic review of the literature examined available evidence regarding the effectiveness of occupational therapy interventions for improving the reading performance of older adults with low vision. We reviewed 32 studies and found strong evidence supporting low vision programs that included occupational therapy and moderately strong evidence supporting the use of electronic magnification. Moderate evidence supported the influence of illumination on reading ability. Limited evidence was found to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 34 publications
0
38
0
2
Order By: Relevance
“…Magnification is the most effective method of compensating for such visual loss. Magnification devices help people with central vision loss perform routine daily tasks such as reading [1][2][3]. Various reading assistance devices, such as head-worn and hand-held optical magnifiers, and electronic magnifiers are commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Magnification is the most effective method of compensating for such visual loss. Magnification devices help people with central vision loss perform routine daily tasks such as reading [1][2][3]. Various reading assistance devices, such as head-worn and hand-held optical magnifiers, and electronic magnifiers are commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Justiss (2013) assessed driving adaptations and interventions, finding insufficient evidence to support current interventions. However, studies by Liu, Brost, Horton, Kenyon, and Mears (2013) and Smallfield, Clem, and Myers (2013) found strong evidence supporting occupational therapy services, adaptive techniques and devices, skills training in addressing instrumental and personal activities of daily living (ADLs), and use of optic and nonoptic devices for reading and participation in ADLs for older adults with low vision. Lysack, Leach, Russo, Paulson, and Lichtenberg (2013) conducted a two-group RCT to investigate the effectiveness of DVD training for occupational therapy clinicians to address mental health issues in older adults and found that such training was beneficial to the clinicians and the quality of care for their patients.…”
Section: Effectiveness Studiesmentioning
confidence: 99%
“…Limited evidence supported the effectiveness of low vision devices over no device use in improving reading performance for older adults with low vision (Smallfield, Schaefer, & Myers, 2013). Low vision devices included nonilluminated and illuminated handheld or stand magnifiers, high-add spectacles, high-plus lenses, telescopes, and electronic magnifiers such as closed-circuit television.…”
Section: Summary Of the Reviewsmentioning
confidence: 99%
“…The evidence is strong that low vision rehabilitation programs that include an occupational therapy practitioner are effective in improving reading and reducing dependence in ADLs and other occupations (Smallfield et al, 2013). Studies providing occupational therapy services incorporated education, training in problem-solving strategies, and instructions in adaptive techniques.…”
Section: Summary Of the Reviewsmentioning
confidence: 99%